The optimum time for reticulocyte count using supravital staining with New Methylene Blue - N Nakkarabandit; K Durmsung; L Manattiraphap; C Nopparatana (Journal of Health Science and Medical Research (JHSMR), 2008)
Reticulocytes are young non-nucleated red cells which retain RNA within the cell. The reticulocyte count is useful to indicate marrow erythropoietic activity and also to classify the causes of anemia disease. The conventional method for enumerating percentage of reticulocytes is by staining with supravital stain by 0.5% New Methylene Blue and incubating at room temperature (25๐C) within 1 hour. With an attempt to reduce the testing time, we studied the percentage of reticulocyte by increasing the temperature (37๐C) by reducing the incubation time (5, 10 and 15 minutes) compared with the conventional method. The results showed no significant difference of the three methods compared with conventional method with p = 0.67, 0.06, 0.15 respectively. There was close correlation between 3 conditions and conventional method with r = 0.994, 0.996, 0.996  (p - value =  < 0.001,  < 0.001,  < 0.001) respectively. In addition, the incubation temperature at 37๐C for 15 minutes showed the best staining quality. We conclude that the method with incubation temperature at 37๐C for 15 minutes was the most suitable method. It could reduce testing time and also increase the quality of staining. This finding is useful for the hematologic laboratory to shorten turn-around time of reticulocyte count test and can result in service improvement.